ANALISIS KINERJA KEUANGAN DEPOSITO MUDHARABAH DI BANK SYARIAH INDONESIA (BSI) - Dayanah, Dewi Rifta; Hayati, Mona; Maulidya, Alda (Cahaya Ilmu Bangsa, 2024)
This study aims to analyze the financial performance of mudharabah deposits at Bank Syariah Indonesia (BSI) using financial indicators such as Capital Adequacy Ratio (CAR), Non-performing Financing (NPF), Return on Assets (ROA), Return oon Equity(ROE), Cost to Income Ratio (CIR), and Financing to Deposit Ratio (FDR). This study uses secondary data in the form BSI’s annual financial statements for the 2021 – 2023 period to evaluate how these indicators affect the stability and competitiveness of mudharabah deposit proofing sharing rates. A descriptive analytical approach is uses to describe the trend of financial performance and identify factors that contribute the performance of mudharabah deposits. This research is expected to be a reference for customers, banking practitioner, and academics in understanding the role of bank financial performance on the management of Islamic products, especially mudharabah deposits. Penelitian ini bertujuan menganalisis kinerja keuangan deposito mudharabah di Bank Syariah Indonesia (BSI) dengan menggunakan indikator keuangan seperti Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Return on Asset (ROA), Return on Equity(ROE), Cost to Income Ratio (CIR) dan Financing to Deposits Ratio (FDR). Penelitian ini menggunakan data sekunder berupa laporan keuangan tahunan BSI periode 2021 – 2023 untuk mengevaluasi bagaimana indikator – indikatir tersebut memengaruhi stabilitas dan daya saing tingkat bagi hasil deposito mudharabah. Pendekatan deskriptif analitis digunakan untuk menggambarkan tren kinerja keuangan dan mengidentifikasi faktor – faktor yang berkontribusi pada kinerja deposito mudharabah. Penelitian ini diharapkan dapat menjadi referensi bagi nasabah, praktisi, perbankan, dan akademisi dalam memahami peran kinerja keuangan bank terhadap pengolaan produk syariah, khusunya deposito mudharabah